FENOLOGI DAN DINAMIKA KANDUNGAN KLOROFIL PADA PEMBUNGAAN DUA SPESIES BELIMBING HUTAN (Averrhoa dolichocarpa DAN Averrhoa leucopetala) - Mangunah, Mangunah; Qayim, Ibnul; Astuti, Inggit Puji (Buletin Kebun Raya, 2013)
Averrhoa dolichocarpa is a wild starfruit from Papua and Averrhoa leucopetala is a wild starfruit from Gorontalo. Both starfruits have unique characters of the leaves, inflorescence, flowers, and fruits. The study was conducted from February 2012 to May 2012 by observing the wild starfruits collections of Bogor Botanical Garden. Innitiation of Averrhoa dolichocarpa inflorescence takes 8-14 days, the small bud growing in 11-15 days, after one day the large bud will open and the anthesis last after 3 days. The fruit will develop and mature after 40-45 days. The flower and fruit drop rate is quite high, mostly caused by strong wind. The chlorophyll content of the leaves are very dynamic and influence by the environment and the wide of the canopy. Whereas initiation of Averrhoa leucopetala inflorescence needs 30-34 days, the small bud growing in 12-15 days, the large flower bud will open after 1 day, anthesis last after 5 days, and the fruit development needs 40-42 days to mature. Anthesis of the flowers occurred at 4:00 to 6:00 a.m. The flower and fruit drop rate is also quite high. The chlorophyll content is more static and tends to increase when the fruit developed.